2015
DOI: 10.3109/17435390.2015.1022887
|View full text |Cite
|
Sign up to set email alerts
|

Surface charge determines the lung inflammogenicity: A study with polystyrene nanoparticles

Abstract: Surface functionalization is a routine process to improve the behavior of nanoparticles (NPs), but the induced surface properties, such as surface charge, can produce differential toxicity profiles. Here, we synthesized a library of covalently functionalized fluorescent polymeric NPs (F-PLNPs) to evaluate the role of surface charge on the acute inflammation and the localization in the lung. Guanidinium-, acetylated-, zwitterionic-, hydroxylated-, PEGylated-, carboxylated- and sulfated-F-PLNPs were synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Furthermore, a comparative study recently demonstrated that CDs prepared from candle soot and subsequently coated with PEI, so they display a net positive charge, were more toxic towards cultured fibroblasts than negatively charged pristine CDs (Havrdova et al 2016). Therefore, as previously reported for silicon- (Shahbazi et al 2013), silver-(El Badawy et al 2011), or polystyrene-based NPs (Kim et al 2016), or for CNTs (Li et al 2013), the surface charge seems to impact on CD safety, a cationic charge being associated with higher toxicological risks. However, the mechanisms involved in the cytotoxicity of cationic CDs remain poorly explored.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, a comparative study recently demonstrated that CDs prepared from candle soot and subsequently coated with PEI, so they display a net positive charge, were more toxic towards cultured fibroblasts than negatively charged pristine CDs (Havrdova et al 2016). Therefore, as previously reported for silicon- (Shahbazi et al 2013), silver-(El Badawy et al 2011), or polystyrene-based NPs (Kim et al 2016), or for CNTs (Li et al 2013), the surface charge seems to impact on CD safety, a cationic charge being associated with higher toxicological risks. However, the mechanisms involved in the cytotoxicity of cationic CDs remain poorly explored.…”
Section: Introductionmentioning
confidence: 68%
“…Surface charge is well known for its drastic influence on nanomaterials biocompatibility (El Badawy et al 2011;Kim et al 2016;Li et al 2013;Shahbazi et al 2013). Regarding CDs, some authors reported that cationic CDs prepared from bPEI25k exhibit some cytotoxicity towards cells of various tissue origins (Liu et al 2012;Pierrat et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such inflammatory mechanisms have been thoroughly investigated and elucidated. To date, it is commonly accepted that the NPs physico-chemical properties (such as composition, size, surface charge, and agglomeration) (Braakhuis, Park, Gosens, De Jong, & Cassee, 2014;Kim et al, 2016;Kreyling, Semmler-Behnke, Takenaka, & Moller, 2013;Madl, Plummer, Carosino, & Pinkerton, 2014;Rotoli et al, 2015), as well as the timing (acute vs. chronic) and route (e.g., intratracheal or intranasal) of administration (Landsiedel, Sauer, Ma-Hock, Schnekenburger, & Wiemann, 2014;Morimoto et al, 2016), strongly influence the lung inflammatory response to NPs (Mohamud et al, 2014). Most of these paradigms have been extrapolated from the data originating from animal studies, which are widely used for evaluating inflammatory responses in inhalation toxicology studies.…”
Section: Introductionmentioning
confidence: 99%
“…As most recently discussed by Gualtieri (2018) in relation to a predictive model of mineral fiber pathogenicity, surface reactivity can play a role in particle/ fiber toxicity. Indeed, attributes such as surface charge have been shown to influence respiratory toxicity of particles such metal oxides (Cho et al 2012) and even polystyrene nanoparticles (Kim et al 2016). In relation to chrysotile, the impact of surface charge on cell injury has been known for some time (Light and Wei 1977) whereby the highly charged surface of chrysotile can cause adverse membrane interactions (as demonstrated by high hemolytic activity).…”
Section: Surface Reactivitymentioning
confidence: 99%